Epidemiologic Study of Trauma Patients Admitted to Shahid Rajaee Hospital of Shiraz, Iran on National, Religious, and Cultural Occasions within 2009-2014 - Mahnaz Yadollahi; Majid Gerami; Narges Shamsedini (Mazandaran University of Medical Sciences, 2017)
Introduction and purpose: Trauma is one of the major cause of mortality and disability in communities and annually leads to the death of millions of people worldwide. Based on the evidence, car accident injuries (especially on religious and cultural events) are at an impressive level in Iran. Regarding this, the aim of the present study was to investigate the prevalence of trauma patients admitted to Shahid Rajai Hospital, and its relationship with religious, cultural, and national occasions, such as Ramadan, Tasua and Ashura, and so forth. Methods: This descriptive, cross-sectional study was conducted on the trauma patients admitted to Shahid Rajai Hospital in Shiraz, Iran, on religious, cultural, and national occasions during 2009-2014. The data were collected through a checklist, including the demographic data, some questions about the mechanism of the accident (i.e., car and motorcycle accidents, pedestrian injuries, assault, as well as gun and knife attacks), and religious occasions of the admission day (e.g., holidays, Wednesday Feast, Yalda, Tasua and Ashura, and Ramadan). The data were analyzed in SPSS version 17 using the descriptive statistics and the frequency distribution table.Results: According to the results, on the celebrations and birthdays, the highest number of trauma patient admission was recorded. In addition, the mean number of hospitalized men was significantly higher than that of the women. There was no significant difference in the mean number of the admissions between the first and second half of Nowruz and between the Martyrs’ Days and birthdays regarding the accident mechanisms of the car accident, motorcycle accident, assaults, falls, and unexpected events. Conclusion: As the findings of the present study indicated, the highest number of the admissinos occurred on the birthdays and celebrations, especially among the males. Therefore, it is suggested that measures be taken to minimize the number of traumatic accidents, especially on holydays, and deliver more care for the pedestrians, motorcyclists, and car drivers in this regard.